P2X7 receptor antagonist A-438079 alleviates oxidative stress of lung in LPS-induced septic rats - Ozkanlar, Seckin; Ulas, Nergis; Kaynar, Ozgur; Satici, Emine (Springer Science and Business Media LLC, 2023)
Sepsis is a deadly systemic inflammatory response of the body against infection resulting in immune response, cell differentiation and organ damage. Endotoxemia is one of the causes of sepsis-related acute respiratory distress and respiratory burst is an important generator of oxidants. Inflammation may be aggravated by overexpression of ATP-gated purinergic receptors (i.e., P2X7R) following cell damage. We aimed to evaluate the effects of P2X7R antagonist A-438079 on lung oxidative status and the receptor expression in endotoxemia of sepsis. Rats were subjected to sepsis by E. coli lipopolysaccharide (LPS) and treated with 15 mg/kg A-438079. The increase in circulatory IL-1β and IL-8 concentrations in LPS group confirmed the systemic inflammatory response to endotoxemia compared with Control groups (p < 0.001). Besides, there was an increase in P2X7R expression in lung tissue after LPS administration. Compared with Control groups, there were significant increases in the values of malondialdehyde (MDA), glutathione (GSH), superoxide dismutase (SOD) and catalase (CAT) (p < 0.001), and myeloperoxidase (MPO) (p < 0.05) in lung tissue of LPS group. P2X7R expression in lung and IL-1β level in blood did not increase in LPS + A-438079 group. A-438079 decreased the lung levels of MDA, GSH, CAT and SOD (p < 0.001), and MPO (p < 0.01) in septic rats. As a result, administration of pathogen-associated LPS led to increased P2X7R expression into lung tissue and elevated lipid peroxidation product MDA with regard to oxidative damage. The P2X7R antagonist A-438079 alleviated the oxidative stress of lung with a balance of tissue oxidant/antioxidant factors in experimental sepsis in rats.
Keywords: Lipopolysaccharides; Oxidative Stress; Purinergic P2X Receptor Antagonists; Superoxide Dismutase; Escherichia coli; Animals; Rats, Wistar; Lung; Endotoxemia; Rats; 3. Good health